2019
DOI: 10.1177/1071181319631467
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Cyber Security Research Published in HFES Proceedings from 1980 to 2018

Abstract: The prevalence of information technology (IT) and widespread use of electronic data storage systems by individuals, corporations, and government branches has prompted investigation into threats to cyber security and data privacy. Within the human factors community, researchers have sought to identify issues related to cyber-attacks and cyber defense and human-centered design. These issues range from placing too much trust in modern technology, to remaining vigilant in the presence of cyber threats such as phis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…In Figure 5, we see the main contributors to Healthcare articles' funding is from military/government sources (43.1%; 72 articles), closely followed by other/non-profit sources (34.1%; 57 articles), academia (13.8%; 23 articles), and industry (9.0%; 15 articles). This is in line with a previous cybersecurity trend analysis (Mouloua et al, 2019) that revealed a similar distribution in military/government and other funding sources. Furthermore, this speaks to a national emphasis on supporting Healthcare research compared to smaller contributions from more decentralized academic or industry sources.…”
Section: Figure 4 Author Affiliations In Healthcare Articlessupporting
confidence: 92%
See 1 more Smart Citation
“…In Figure 5, we see the main contributors to Healthcare articles' funding is from military/government sources (43.1%; 72 articles), closely followed by other/non-profit sources (34.1%; 57 articles), academia (13.8%; 23 articles), and industry (9.0%; 15 articles). This is in line with a previous cybersecurity trend analysis (Mouloua et al, 2019) that revealed a similar distribution in military/government and other funding sources. Furthermore, this speaks to a national emphasis on supporting Healthcare research compared to smaller contributions from more decentralized academic or industry sources.…”
Section: Figure 4 Author Affiliations In Healthcare Articlessupporting
confidence: 92%
“…Past analyses of Healthcare trends ranged from 1999 to 2009, and 2010 to 2017 (Decheneaux et al, 2011;Stowers & Mouloua, 2018). The structure of the present study was modeled more closely after previous trend analyses in cybersecurity (Mouloua et al, 2019) and unmanned aerial vehicles in the HFES Proceedings, using a design which has demonstrated effective in illustrating the distribution of articles over categorical characteristics and time in the literature. In our study, we used the same trend analysis approach as these prior studies in order to maintain continuity and to demonstrate consistent changes over time across numerous subfields in Human Factors.…”
Section: Introductionmentioning
confidence: 99%
“…In academia, the awareness for research in the field of cybersecurity has also grown. For instance, Mouloua, Ferraro, Mouloua, Matthews, and Copeland (2019) analyzed the articles published in the Proceedings of the Human Factors and Ergonomics Society (HFES) from 1980 to 2018. They showed that 73% of articles related to cybersecurity published in that almost 40-year span were written in the last nine years.…”
Section: Introductionmentioning
confidence: 99%
“…In academia, the awareness for research in the field of cybersecurity has also grown. For instance, Mouloua et al analyzed the articles published in the Proceedings of the Human Factors and Ergonomics Society (HFES) from 1980 to 2018 [2]. They showed that 73% of articles related to cybersecurity published in that almost 40-year span were written in the last nine years.…”
Section: Introductionmentioning
confidence: 99%